2011
DOI: 10.3748/wjg.v17.i33.3842
|View full text |Cite
|
Sign up to set email alerts
|

Management of acquired bronchobiliary fistula: A systematic literature review of 68 cases published in 30 years

Abstract: The clinical diagnosis of BBF can be established by sputum analysis. Careful assessment of this condition is needed before therapeutic procedure. Invasive approaches should be considered only when non-invasive methods failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
210
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(217 citation statements)
references
References 51 publications
2
210
1
4
Order By: Relevance
“…BBF is an abnormal communication between the bile duct and the bronchial tree, and can arise from hydatid disease, trauma, bile duct obstruction, tumor invasion and iatrogenic injuries caused by procedures such as TACE and RFA (10,11). The complication rate of RFA for HCC is 0.6-10% (4,12); however, only sporadic cases of BBF as a complication of RFA have been reported (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…BBF is an abnormal communication between the bile duct and the bronchial tree, and can arise from hydatid disease, trauma, bile duct obstruction, tumor invasion and iatrogenic injuries caused by procedures such as TACE and RFA (10,11). The complication rate of RFA for HCC is 0.6-10% (4,12); however, only sporadic cases of BBF as a complication of RFA have been reported (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Once BBF develops most frequent symptoms include fever, irritating productive cough, chest pain, right upper abdominal pain and jaundice [2,5,7]. Bile behaves as a strong irritant when present outside the billiary channel and gastrointestinal system.…”
Section: Discussionmentioning
confidence: 99%
“…This patient had failed arterial chemotherapies, radiofrequency ablations, chemoembolization, and a right lobectomy. The bilopytsis has resolved after histoacryl embolization, but patient died from biliary obstruction and hepatic failure three months later [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] With advancements in modern medicine, minimally invasive techniques have been developed for the direct intervention to a BBF as a means of therapy. Mukada et al reported embolization of a BBF with the placement of microcoils and application of cyanoacrylate glue through endoscopic retrograde cholangiopancreatography.…”
Section: Discussionmentioning
confidence: 99%